Antenatal Antibiotic Exposure Affects Enteral Feeding, Body Growth, and Neonatal Infection in Preterm Infants: A Retrospective Study - Luo, Ping; Zhang, Kun; Chen, You; Geng, Xiuwen; Wu, Tong; Li, Li; Zhou, Ping; Jiang, Ping-Ping; Ma, Liya (Frontiers in Pediatrics, 2021)
Background: Antibiotics are widely prescribed by obstetricians, which exposes a large number of infants to antenatal antibiotic exposure (AAB). The effect of AAB on various aspects of neonatal development of preterm infants remains unclear. Methods: In this retrospective study, infants born with gestational age (GA) between 22+0 and 36+6 weeks at our unit from 2017 to 2019 were included. Multivariable analysis was adopted to examine the associations between AAB exposure and various outcomes related to the enteral feeding process, body growth, and neonatal infection after adjusting for potential confounders. Further sub-analysis on the exposure level of AAB and stratified analysis by GA (<34 vs. ≥34 weeks) were also conducted. Results: In this cohort comprising 2,543 preterm infants, AAB was associated with decreased risks of feeding intolerance (odds ratio [OR]: 0.63, 95% confidence interval [CI]: 0.48–0.82) and neonatal infection (OR: 0.63, 95%CI: 0.41–0.94). Higher AAB exposure level was associated with higher Z scores of birth weight (β = 0.37, 95%CI: 0.27–0.47), but lower Δbodyweight Z-scores (β = -0.20, 95%CI: -0.27 to -0.13). AAB was positively associated with the parameters related to body growth in infants with GA <34 weeks, but negatively associated in those with GA ≥34 weeks. Conclusions: AAB exposure affects the enteral feeding process and neonatal infection. The effects on body growth vary by the exposure level of AAB and GA of infants. A well-designed prospective and preferably multi-centre study with predefined parameters is required to confirm our findings. Keywords: antenatal antibiotic exposure, preterm infants, enteral feeding, body growth, neonatal infection